2020
DOI: 10.1177/0954408920925017
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for calculating limit deceleration of flexible hoisting system: A case study of mine hoist

Abstract: Mine hoist is a typical flexible lifting system. Due to the cable flexibility, the system is prone to severe shocks and even slippage during emergency braking. To establish a safe emergency braking operation for mine hoist, retarded velocity should be less than the limit deceleration value. The simplified mathematical model shows that the system dynamic response along the longitudinal axis of the wire rope (longitudinal dynamics) is a typical second-order underdamped one. Due to the inherent characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, the traditional PI and traditional backstepping (BT) controller are chosen as the comparative experiments to illustrate the advantage of the developed controller in this paper. Referring to the braking performance requirements of the JKMD 3.25 × 4 II mine hoist in Huang et al 37 two performance requirements for braking control on the simulation test rig are summarised. The first one is that the tension of wire rope shall not exceed 1250 N , and another one is that the peak acceleration shall not exceed 0 . 25 m / s 2 during braking with lifting load 100 kg and desired deceleration 0 . 1 m / s 2 .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Furthermore, the traditional PI and traditional backstepping (BT) controller are chosen as the comparative experiments to illustrate the advantage of the developed controller in this paper. Referring to the braking performance requirements of the JKMD 3.25 × 4 II mine hoist in Huang et al 37 two performance requirements for braking control on the simulation test rig are summarised. The first one is that the tension of wire rope shall not exceed 1250 N , and another one is that the peak acceleration shall not exceed 0 . 25 m / s 2 during braking with lifting load 100 kg and desired deceleration 0 . 1 m / s 2 .…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…He [9] has also studied the longitudinal rope dynamics in a friction hoisting system and its coupling effect with friction transmission and concluded that the tension fluctuates obviously, and the dynamic tension regime expands with the friction coefficient increase. Huang et al [10] have simplified the longitudinal vibration model of a mine hoisting as a second-order underdamped system and obtained its dynamic response in the slipping and unslippage state for a safe emergency barking operation. Wu and Kou [11] have established the longitudinal-transverse model of mine friction hoist by using of Hamilton's principle, and the modified Galerkin's method has been used to discretize partial differential Equations.…”
Section: Introductionmentioning
confidence: 99%